Estimating cognitive load during self-regulation of brain activity and neurofeedback with therapeutic brain-computer interfaces - Bauer, Robert; Gharabaghi, Alireza (Frontiers in Behavioral Neuroscience, 2015)
Neurofeedback training with brain-computer interfaces is currently studied in a variety of neurological and neuropsychiatric conditions to reduce disorder-specific symptoms. For this purpose, a variety of classification algorithms have been explored to distinguish different brain states. These neural states, e.g. self-regulated brain activity versus rest, are separated by setting a threshold parameter. Measures such as the maximum classification accuracy have been introduced to evaluate the performance of these algorithms. Interestingly, the very same measures are often used to estimate the subject’s ability to perform brain self-regulation. This is surprising, as the goal of improving the tool that differentiates brain states is different from the aim of optimizing neurofeedback for the subject who performs brain self-regulation. For the latter, knowledge about mental resources and work load is essential to adapt the difficulty of the intervention. In this context, we apply an analytical method and provide empirical data to determine the zone of proximal development as a measure of a subject’s cognitive resources and the instructional efficacy of neurofeedback. This approach is based on a reconsideration of item-response theory and cognitive load theory for instructional design, and combines them with the classification accuracy curve as a measure of BCI performance.